Zonisamide: Clinical Efficacy and Safety in Refractory Partial Epilepsy - Jedsadayanmata, Arom (Asian Health, Science and Technology Reports, 2006)
Epilepsy is a chronic central nervous system disorder, characterized by the recurrence of seizures secondary to excessive and abnormal electrical discharge in the brain tissue. Successful management of epilepsy requires suppression of seizure recurrence by antiepileptic drugs either as single-agent or combination. Zonisamide (ZNS) is 1,2-benzisoxazole-3-methanesulfonamide that has been shown to possess antiseizure activity against partial-onset epilepsy in various animal models. In four randomized, double-blind, placebo-controlled trials, ZNS was shown to be effective in reducing the median frequency of seizures in patients with refractory partial epilepsy while receiving other concurrent antiepileptic drugs (AEDs). A further reduction of 20-50% in seizure frequency was observed at different doses and this was significantly different from placebo. Moreover, the responder rate defined as the proportion of patients achieving more than 50% reduction in median seizure frequency was consistently higher in patients receiving ZNS than placebo. Commonly associated adverse effects of ZNS therapy include somnolence, dizziness, anorexia, and weight loss. The current licensed indication for ZNS in the U.S. is as adjunctive therapy for partial epilepsy in adults over 16 years old. The appropriate starting dose is 100 mg/day and the dose should be titrated in 100-mg increment per day biweekly to the effective maintenance dosage without intolerable adverse effects. The recommended therapeutic serum concentration of ZNS has not been established; however, in most clinical trials the serum concentration of ZNS was usually maintained at 20-30 µg/ml and was shown to be effective.